Composite sodium supplementing material, preparation method and application thereof, and positive pole piece
By introducing conductive carbon materials and nanometal oxides into the positive sodium supplementing agent of sodium ion battery, the composite sodium supplementing material is prepared, and the problem of insufficient desodium voltage and capacity of existing sodium supplementing agents is solved, and more efficient sodium ion battery performance is achieved.
Patent Information
- Application Number
- CN202411953602.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-11
AI Technical Summary
The desodium voltage and capacity of the positive sodium supplement agent of existing sodium ion batteries limit their industrial applications, especially the capacity of sodium mortar is low and the desodium voltage is not suitable.
By mixing sodium cubate, conductive carbon material and nanometal oxide in liquid phase, sanding and spray drying, a composite sodium supplement material is prepared. The introduction of conductive carbon materials and nanometal oxides reduces the decomposition potential of sodium cuminate, improves its utilization efficiency and sodium supplementation effect.
This method effectively improves the desodium voltage and capacity of composite sodium supplement materials, improves the comprehensive performance of sodium ion batteries, and helps promote the industrialization and development of sodium-electrode materials.
Smart Images

Figure CN119812296A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of sodium ion battery manufacturing, and in particular to a composite sodium supplement material, a preparation method and application thereof, and a positive electrode sheet. Background Art
[0002] Among existing battery technologies, lithium-ion batteries have dominated the field of new energy batteries due to their advantages such as high energy efficiency and mature technology. However, the global lithium resources are scarce (only 0.002% abundance in the earth's crust) and unevenly distributed, which cannot meet the growing demand. In addition, the current high price of lithium ore has increased the cost of lithium-ion batteries and cannot be used on a large scale. Therefore, people have begun to devote themselves to the development of new low-cost battery systems, such as sodium-ion batteries. Na and Li belong to the same group IA elements and have similar physical and chemical properties. Therefore, the working principle of sodium-ion batteries is similar to that of lithium-ion batteries. In addition, sodium resources are abundant (2.64% abundance in the earth's crust) and widely distributed. There is no limitation of resource shortage, which can greatly reduce the cost of sodium-ion batteries.
[0003] Sodium-ion batteries are an emerging battery technology that can use widely available and inexpensive raw materials compared to lithium-ion batteries, and can use existing lithium-ion battery production methods, which is expected to achieve rapid expansion.
[0004] During the first charge of a sodium battery, a stable solid electrolyte interface (SEI) membrane will be irreversibly formed on the negative electrode surface, which can transfer sodium ions while effectively isolating the electrolyte from entering, thus maintaining the stability of the battery operation. However, the SEI membrane formation process is accompanied by a large amount of irreversible loss of active sodium, resulting in a decrease in coulombic efficiency. Therefore, it is necessary to explore appropriate pre-sodiumization methods to compensate for the irreversible loss of active sodium in the first cycle.
[0005] At present, the sodium supplementation methods are divided into positive electrode sodium supplementation and negative electrode sodium supplementation methods; the positive electrode sodium supplementation method is simple to operate and has a good sodium supplementation effect, and has a better development prospect. At present, the positive electrode sodium supplements used in the industry are sodium carbonate, sodium oxalate and sodium squarate, but these sodium supplements have some problems, such as the small actual capacity of sodium carbonate; the sodium oxalate de-sodium voltage is too high (4.2V), which is higher than the working voltage of sodium ion batteries (generally <3.9V); although the sodium de-sodium voltage (3.6V) of sodium squarate is suitable for the working voltage of sodium ion batteries, its capacity is relatively low (340mAh / g); that is, the sodium de-sodium voltage and capacity of the positive electrode sodium supplement have always been the problem restricting the industrialization of the sodium supplement.
[0006] Therefore, a new sodium supplement material needs to be provided to meet application requirements. Summary of the invention
[0007] In order to solve the above technical problems, the present disclosure provides a composite sodium supplement material and a preparation method and application thereof.
[0008] In a first aspect, the present disclosure provides a method for preparing a composite sodium supplement material, the preparation method comprising the following steps:
[0009] Sodium squarate, conductive carbon material and nano metal oxide are mixed in liquid phase to obtain a mixed slurry, and the mixed slurry is sand-milled and spray-dried to obtain the composite sodium supplement material.
[0010] As a preferred technical solution of the present disclosure, the mass of the nano metal oxide is 1-10% of the mass of the sodium squarate.
[0011] As a preferred technical solution of the present disclosure, based on the total mass of the conductive carbon material and sodium squarate being 100%, the content of the sodium squarate is 50-90%.
[0012] As a preferred technical solution of the present disclosure, the conductive carbon material includes any one of porous carbon nanotubes, Ketjen black, porous carbon aerogel or graphene, or a combination of at least two of them.
[0013] As a preferred technical solution of the present disclosure, the nano metal oxide includes any one or a combination of at least two of manganese dioxide (MnO2), titanium dioxide (TiO2), stannous oxide (SnO), aluminum oxide (Al2O3), copper oxide (CuO), zinc oxide (ZnO), molybdenum dioxide (MoO2), nickel oxide (NiO) or cobalt oxide (CoO), and preferably includes any one or a combination of at least two of stannous oxide (SnO), aluminum oxide (Al2O3), copper oxide (CuO), zinc oxide (ZnO), nickel oxide (NiO) or cobalt oxide (CoO).
[0014] As a preferred technical solution of the present disclosure, the size of the nano metal oxide is ≤30nm.
[0015] As a preferred technical solution of the present disclosure, the sanding time is 60-240 minutes.
[0016] As a preferred technical solution of the present disclosure, after the sand grinding, the D50 of the slurry is 100-500nm.
[0017] As a preferred technical solution of the present disclosure, the spray drying temperature is 120-200°C.
[0018] As a preferred technical solution of the present disclosure, the slurry also includes a dispersant.
[0019] As a preferred technical solution of the present disclosure, the added amount of the dispersant is 0.5-2% of the mass of the conductive carbon material.
[0020] As a preferred technical solution of the present disclosure, the dispersant includes polyvinyl pyrrolidone and / or polyethylene glycol.
[0021] As a preferred technical solution of the present disclosure, the solvent used in the slurry is water.
[0022] As a preferred technical solution of the present disclosure, the preparation method comprises:
[0023] (1) mixing sodium squarate and a dispersant in water to obtain a saturated aqueous solution;
[0024] (2) dispersing the conductive carbon material and the nano-metal oxide in the saturated aqueous solution to obtain a mixed slurry;
[0025] (3) The mixed slurry is sand-milled and spray-dried to obtain the composite sodium supplement material.
[0026] In a second aspect, the present disclosure provides a composite sodium supplement material prepared using the preparation method described in the first aspect.
[0027] In a third aspect, the present disclosure provides an application of the composite sodium supplement material described in the second aspect in a sodium ion battery, preferably in a positive electrode plate of a sodium ion battery.
[0028] In a fourth aspect, the present disclosure provides a positive electrode plate, comprising a positive electrode active material and the composite sodium supplement material described in the second aspect.
[0029] As a preferred technical solution of the present disclosure, the addition amount of the composite sodium supplement material is 0.5-5% of the positive electrode active material.
[0030] Compared with the prior art, the technical solution provided by the embodiments of the present disclosure has the following advantages:
[0031] (1) The preparation method provided by the present disclosure simultaneously introduces conductive carbon materials and nano-metal oxides, which effectively improves the utilization efficiency and sodium supplementation effect of sodium squarate.
[0032] (2) The preparation method provided by the present disclosure has the characteristics of simple process, controllable process, and large-scale preparation.
[0033] (3) The composite sodium supplement material obtained by the preparation method provided in the present disclosure can be applied to sodium ion batteries to effectively supplement the sodium loss in the first cycle, improve the comprehensive performance of the battery, and be beneficial to the performance of the positive electrode material.
[0034] (4) The composite sodium supplement material obtained by the preparation method provided in the present disclosure has high versatility in the field of sodium electricity, and can help promote the industrialization and development of sodium battery positive electrode sheets. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present disclosure and, together with the description, serve to explain the principles of the present disclosure.
[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0037] Figure 1 is a flow chart for preparing the composite sodium supplement material disclosed in the present invention;
[0038] Figure 2 1 and 2. The half-cell charging curves of the composite sodium supplement materials prepared in Example 1 and Comparative Examples 1-3. DETAILED DESCRIPTION
[0039] In order to more clearly understand the above-mentioned objectives, features and advantages of the present disclosure, the scheme of the present disclosure will be further described below. It should be noted that the embodiments of the present disclosure and the features in the embodiments can be combined with each other without conflict.
[0040] In the following description, many specific details are set forth to facilitate a full understanding of the present disclosure, but the present disclosure may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present disclosure, rather than all of the embodiments.
[0041] Among the existing technologies, the positive electrode sodium supplementation method has a good development prospect. However, the sodium removal voltage and capacity of the currently used positive electrode sodium supplement agents have always been a problem that restricts the industrialization of sodium supplement agents. To this end, the present disclosure provides a preparation method of a dual-catalyst composite sodium supplement material.
[0042] In a first aspect, the present disclosure provides a method for preparing a dual-catalytic composite sodium supplement material, the preparation method comprising the following steps:
[0043] Sodium squarate, conductive carbon material and nano metal oxide are mixed in liquid phase to obtain a mixed slurry, and the mixed slurry is sand-milled and spray-dried to obtain the composite sodium supplement material.
[0044] In the present disclosure, conductive carbon material and nano metal oxide are simultaneously introduced into sodium squarate, and the two act together on the sodium squarate, wherein the nano metal oxide can provide a large number of sodium squarate nucleation sites, so that the sodium squarate is deposited when it precipitates from the solution, and the conductive carbon material is introduced into the system at the same time, so that the sodium squarate can be combined with and attached to the internal holes or surface of the conductive carbon material. That is, in the present disclosure, the introduction of conductive carbon material and nano metal oxide can, on the one hand, avoid the sodium squarate from being too large in size, and on the other hand, provide a conductive and catalytic network with a high specific surface area, reduce the sodium removal energy barrier of the sodium squarate, play a role in promoting the transmission of electrons and the decomposition of the sodium squarate, and help to improve the utilization efficiency and sodium supplementation effect of the composite sodium supplement.
[0045] As a preferred technical solution of the present disclosure, the mass of the nano metal oxide is 1-10% of the mass of the sodium squarate, for example, 1%, 3%, 4%, 6%, 7%, 9%, 10%, etc.
[0046] As a preferred technical solution of the present disclosure, based on the total mass of the conductive carbon material and sodium squarate as 100%, the content of the sodium squarate is 50-90%, for example, 50%, 60%, 70%, 80%, 90%, etc.
[0047] As a preferred technical solution of the present disclosure, the conductive carbon material includes any one of porous carbon nanotubes, Ketjen black, porous carbon aerogel or graphene, or a combination of at least two of them.
[0048] As a preferred technical solution of the present disclosure, the nano metal oxide includes any one of MnO2, TiO2, SnO, Al2O3, CuO, ZnO, MoO2, NiO or CoO or a combination of at least two of them, preferably including any one of SnO, Al2O3, CuO, ZnO, NiO or CoO or a combination of at least two of them, which has a better effect; the size of the nano metal oxide is ≤30nm, for example, 10nm, 20nm, 30nm, etc.
[0049] In the present disclosure, the introduced conductive carbon material and nano metal oxide both help to reduce the decomposition potential of sodium squarate, thereby promoting the decomposition of sodium squarate.
[0050] As a preferred technical solution of the present invention, the sand grinding time is 60-240min, for example, 60min, 90min, 120min, 170min, 200min, 240min; after the sand grinding, the D50 of the slurry is 100-500nm, for example, 100nm, 150nm, 200nm, 400nm, 450nm, 500nm, etc.
[0051] As a preferred technical solution of the present disclosure, the spray drying temperature is 120-200°C, for example, 120°C, 140°C, 150°C, 180°C, 200°C, etc.
[0052] As a preferred technical solution of the present disclosure, the added amount of the dispersant is 0.5-2% of the mass of the conductive carbon material, for example, 0.5%, 0.8%, 0.9%, 1%, 1.3%, 1.8%, 2%, etc.
[0053] As a preferred technical solution of the present disclosure, the dispersant includes polyvinyl pyrrolidone and / or polyethylene glycol.
[0054] As a preferred technical solution of the present disclosure, the solvent used in the slurry is water.
[0055] As a preferred technical solution of the present disclosure, Figure 1 As shown, the preparation method comprises:
[0056] (1) mixing sodium squarate and a dispersant in water to obtain a saturated aqueous solution;
[0057] (2) dispersing the conductive carbon material and the nano-metal oxide in the saturated aqueous solution to obtain a slurry;
[0058] (3) The slurry is sand-milled and spray-dried to obtain the composite sodium supplement material.
[0059] The preparation method provided by the present invention has simple process and controllable process, and can realize large-scale preparation.
[0060] As a specific embodiment of the present disclosure, the preparation method comprises:
[0061] (1) mixing sodium squarate and a dispersant in water to obtain a saturated aqueous solution, wherein the amount of the dispersant added is 0.5-2% of the conductive carbon material;
[0062] (2) dispersing the conductive carbon material and the nano-metal oxide in the saturated aqueous solution to obtain a slurry, wherein the amount of the conductive carbon material added is 10-50% of the sum of the mass of the sodium squarate and the conductive carbon material, and the mass of the nano-metal oxide is 1-10% of the mass of the sodium squarate;
[0063] (3) The slurry is sand-milled for 60-240 min, and the particle size D50 of the slurry after sand-milling is 100-500 nm, and then spray-dried at 120-200° C. to obtain the composite sodium supplement material.
[0064] The preparation method provided by the present disclosure effectively improves the utilization efficiency and sodium supplementation effect of sodium squarate, improves the comprehensive performance of the battery, and can help promote the industrialization and development of sodium battery positive electrode materials.
[0065] In a second aspect, the present disclosure provides a composite sodium supplement material prepared using the preparation method described in the first aspect.
[0066] The composite sodium supplement material provided by the present disclosure includes sodium supplement active material sodium squarate, nano metal oxide catalyst and conductive carbon material; wherein: sodium squarate, nano metal oxide and conductive carbon material are closely combined. The conductive carbon material and nano metal oxide together provide a highly efficient conductive and catalytic structure, which can reduce the sodium removal energy barrier of sodium squarate, thereby reducing the sodium removal potential of the composite sodium supplement material and effectively improving the utilization efficiency of sodium squarate.
[0067] The composite sodium-supplementing material provided by the present invention has a small active ingredient particle size, good conductivity, and low decomposition potential, has an excellent sodium-supplementing effect, and can be used for sodium supplementation of positive electrode plates.
[0068] The composite sodium supplement material provided by the present invention has the advantages of suitable sodium removal voltage and high capacity. Applying it to sodium ion batteries can effectively improve the comprehensive performance of the battery.
[0069] In a third aspect, the present disclosure provides a positive electrode plate, comprising a positive electrode active material and the composite sodium supplement material described in the second aspect.
[0070] As a preferred technical solution of the present disclosure, the addition amount of the composite sodium supplement material is 0.5-5% of the positive electrode active material, for example, 0.5%, 0.6%, 1%, 3.5%, 4%, 5%, etc.
[0071] In a fourth aspect, the present disclosure may also provide a sodium ion battery comprising the positive electrode sheet described in the third aspect.
[0072] The following is described by way of specific examples:
[0073] Example 1
[0074] This embodiment provides a method for preparing a composite sodium supplement material, as follows:
[0075] (1) Sodium squarate and a dispersant are mixed in water to obtain a saturated aqueous solution, wherein:
[0076] The dispersant is polyvinyl pyrrolidone, and the added amount is 1% of the conductive carbon material;
[0077] (2) The conductive carbon material and the nano-metal oxide are dispersed in the saturated aqueous solution to obtain a mixed slurry, wherein:
[0078] The conductive carbon material is porous carbon nanotubes, and the mass ratio of sodium squarate to the porous carbon nanotubes is 7:3; the nano metal oxide is nano SnO, and the added amount is 3% of the mass of the sodium squarate;
[0079] (3) The mixed slurry is sand-milled for 120 minutes, and the particle size D50 of the slurry after sand-milling is about 200 nm, and then spray-dried at 150° C. to obtain the composite sodium supplement material.
[0080] Example 2
[0081] This embodiment provides a method for preparing a composite sodium supplement material, as follows:
[0082] (1) Sodium squarate and a dispersant are mixed in water to obtain a saturated aqueous solution, wherein:
[0083] The dispersant is polyethylene glycol, and the added amount is 0.5% of the conductive carbon material;
[0084] (2) The conductive carbon material and the nano-metal oxide are dispersed in the saturated aqueous solution to obtain a mixed slurry, wherein:
[0085] The conductive carbon material is porous carbon aerogel, and the mass ratio of sodium squarate to the porous carbon aerogel is 8:2; the nano metal oxide is nano SnO, and the addition amount is 1% of the mass of sodium squarate;
[0086] (3) The mixed slurry is sand-milled for 60 minutes, and the particle size D50 of the slurry after sand-milling is about 450 nm, and then spray-dried at 120° C. to obtain the composite sodium supplement material.
[0087] Example 3
[0088] This embodiment provides a method for preparing a composite sodium supplement material, as follows:
[0089] (1) Sodium squarate and a dispersant are mixed in water to obtain a saturated aqueous solution, wherein:
[0090] The dispersant is polyvinyl pyrrolidone, and the added amount is 2% of the conductive carbon material;
[0091] (2) The conductive carbon material and the nano-metal oxide are dispersed in the saturated aqueous solution to obtain a mixed slurry, wherein:
[0092] The conductive carbon material is graphene, and the mass ratio of sodium squarate to graphene is 9:1; the nano metal oxide is nano CoO, and the added amount is 10% of the mass of sodium squarate;
[0093] (3) The mixed slurry is sand-milled for 240 minutes, and the particle size D50 of the slurry after sand-milling is about 100 nm, and then spray-dried at 180° C. to obtain the composite sodium supplement material.
[0094] Example 4
[0095] This embodiment provides a method for preparing a composite sodium supplement material, as follows:
[0096] (1) Sodium squarate and a dispersant are mixed in water to obtain a saturated aqueous solution, wherein:
[0097] The dispersant is polyvinyl pyrrolidone, and the added amount is 0.5% of the conductive carbon material;
[0098] (2) The conductive carbon material and the nano-metal oxide are dispersed in the saturated aqueous solution to obtain a mixed slurry, wherein:
[0099] The conductive carbon material is Ketjen black, and the mass ratio of sodium squarate to Ketjen black is 5:5; the nano metal oxide is nano Al2O3, and the addition amount is 1% of the mass of sodium squarate;
[0100] (3) The mixed slurry is sand-milled for 120 minutes, and the particle size D50 of the slurry after sand-milling is about 250 nm, and then spray-dried at 200° C. to obtain the composite sodium supplement material.
[0101] Example 5
[0102] This embodiment provides a method for preparing a composite sodium supplement material.
[0103] The difference from Example 4 is that in this example, the mass ratio of sodium squarate to the conductive carbon material is 4:6.
[0104] Example 6
[0105] This embodiment provides a method for preparing a composite sodium supplement material.
[0106] The difference from Example 4 is that in this example, the mass ratio of sodium squarate to the conductive carbon material is 9.5:0.5.
[0107] Example 7
[0108] This embodiment provides a method for preparing a composite sodium supplement material.
[0109] The difference from Example 4 is that in this example, the added amount of the nano metal oxide is 0.5% of the mass of the sodium squarate.
[0110] Example 8
[0111] This embodiment provides a method for preparing a composite sodium supplement material.
[0112] The difference from Example 4 is that in this example, the added amount of the nano metal oxide is 20% of the mass of the sodium squarate.
[0113] Example 9
[0114] This embodiment provides a method for preparing a composite sodium supplement material.
[0115] The difference from Example 4 is that in this example, the particle size D50 of the slurry after sand grinding is about 50 nm.
[0116] Example 10
[0117] This embodiment provides a method for preparing a composite sodium supplement material.
[0118] The difference from Example 4 is that in this example, the particle size D50 of the slurry after sand grinding is about 700 nm.
[0119] Embodiment 11
[0120] This embodiment provides a method for preparing a composite sodium supplement material.
[0121] The difference from Example 4 is that in this example, the nano metal oxide is nano MnO2.
[0122] Comparative Example 1
[0123] This comparative example provides a sodium supplement material and a preparation method thereof.
[0124] The difference from Example 1 is that in this comparative example, no nano metal oxide is added. The specific preparation method is as follows:
[0125] (1) Sodium squarate and a dispersant are mixed in water to obtain a saturated aqueous solution, wherein:
[0126] The dispersant is polyvinyl pyrrolidone, and the added amount is 1% of the conductive carbon material;
[0127] (2) The conductive carbon material is dispersed in the saturated aqueous solution to obtain a mixed slurry, wherein:
[0128] The conductive carbon material is porous carbon nanotubes, and the mass ratio of sodium squarate to the porous carbon nanotubes is 7:3;
[0129] (3) The mixed slurry is sand-milled for 120 minutes, and the particle size D50 of the slurry after sand-milling is about 200 nm, and then spray-dried at 150° C. to obtain the composite sodium supplement material.
[0130] Comparative Example 2
[0131] This comparative example provides a sodium supplement material and a preparation method thereof.
[0132] The difference from Example 1 is that in this comparative example, no conductive carbon material is added. The specific preparation method is as follows:
[0133] (1) Sodium squarate and a dispersant are mixed in water to obtain a saturated aqueous solution, wherein:
[0134] The dispersant is polyvinyl pyrrolidone, and the added amount is 1% of the conductive carbon material;
[0135] (2) dispersing the nano-metal oxide in the saturated aqueous solution to obtain a mixed slurry, wherein:
[0136] The nano metal oxide is nano TiO2, and the nano TiO2 is 3% of the mass of sodium squarate;
[0137] (3) The mixed slurry was sand-milled for 120 minutes, and then spray-dried at 150° C. to obtain the composite sodium supplement material.
[0138] Comparative Example 3
[0139] This comparative example provides a sodium supplement material and a preparation method thereof.
[0140] The difference from Example 1 is that in this comparative example, no nano metal oxide and conductive carbon material are added, and the specific preparation method is as follows:
[0141] (1) Sodium squarate and a dispersant are mixed in water to obtain a saturated aqueous solution, wherein:
[0142] The dispersant is polyvinyl pyrrolidone, and the added amount is consistent with that in Example 1;
[0143] (2) The saturated aqueous solution was sand-milled for 120 min, and then spray-dried at 150° C. to obtain the composite sodium supplement material.
[0144] Performance Testing
[0145] The samples provided in the embodiments and comparative examples were tested for performance as follows:
[0146] Half-cell charging test of composite sodium-supplementing materials: 80% composite sodium-supplementing materials, 10% SuperP, 10% PVDF and NMP were mixed respectively, and the composite sodium-supplementing material pole pieces were obtained by homogenization, coating, drying and rolling. The metallic sodium sheet was used as the counter electrode, 5 vol% fluoroethylene carbonate was added to the 1M NaClO4 / propylene carbonate solution as the electrolyte, and glass fiber was used as the diaphragm. The button cells were assembled in a high-purity argon atmosphere glove box, and the charging test was carried out in the voltage window of 2.7-4.2V.
[0147] Composite sodium-supplementing materials are used in half-cell performance test of sodium-ion batteries: sodium ferric pyrophosphate (NFPP), SuperP, and PVDF are mixed in a mass ratio of 8:1:1, and 5% of the mass of NFPP composite sodium-supplementing materials are added. The above mixture is mixed with NMP, and the positive electrode sheet of NFPP is obtained by homogenization, coating, drying, and rolling. The metallic sodium sheet is used as the counter electrode, 5 vol% fluoroethylene carbonate is added to the 1M NaClO4 / propylene carbonate solution as the electrolyte, and glass fiber is used as the diaphragm. The button cells are assembled in a high-purity argon atmosphere glove box, and electrochemical tests are carried out in a voltage window of 1.8-4.2V.
[0148] Composite sodium-supplementing materials are used in full-cell performance testing of sodium-ion batteries: sodium ferric pyrophosphate (NFPP), SuperP, and PVDF are mixed in a mass ratio of 8:1:1, and 5% of the mass of NFPP composite sodium-supplementing materials are added, and the above mixture is mixed with NMP. The NFPP positive electrode sheet is obtained by homogenization, coating, drying, and rolling. The negative electrode sheet is prepared with commercial hard carbon, 5 vol% fluoroethylene carbonate is added to a 1M NaClO4 / propylene carbonate solution as an electrolyte, and glass fiber is used as a diaphragm. Button cells are assembled in a high-purity argon atmosphere glove box, and electrochemical tests are carried out in a voltage window of 1.8-3.8V.
[0149] The test results are as follows:
[0150] Figure 2 The half-cell charging curves of the composite sodium supplement materials prepared in Example 1 and Comparative Examples 1-3;
[0151] Combination Figure 2 It can be seen that when the composite sodium-supplementing material is charged, the composite sodium-supplementing material provided in Example 1 of the present disclosure has the lowest decomposition voltage and the highest capacity, indicating that the conductive carbon network and the nano-metal oxide jointly play a role in reducing the sodium removal energy barrier, promoting the decomposition of sodium squarate, and improving the utilization rate of sodium squarate.
[0152] Test data see Table 1
[0153] Table 1
[0154]
[0155]
[0156] It can be seen from the examples and performance tests that the composite sodium supplement material provided by the present disclosure has a suitable decomposition voltage and a better comprehensive sodium supplement effect.
[0157] From the comparison between Example 4 and Examples 5-11, it can be seen that when the nano metal oxide, the conductive carbon material and the sodium squarate are within the preferred range of the present disclosure, and the slurry after sand grinding is within the preferred range of the present disclosure, the performance of the obtained composite sodium supplement material is better.
[0158] From the comparison between the embodiment and the comparative example, it can be seen that when sodium squarate is used as the sodium supplement material, the introduction of conductive carbon material and nano metal oxide at the same time can maximize the capacity of the sodium supplement material for better application.
[0159] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0160] The above description is only a specific embodiment of the present disclosure, so that those skilled in the art can understand or implement the present disclosure. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present disclosure. Therefore, the present disclosure will not be limited to the embodiments described herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a composite sodium supplement material, characterized in that: The preparation method comprises the following steps: Sodium squarate, conductive carbon material and nano metal oxide are mixed in liquid phase to obtain a mixed slurry, and the mixed slurry is sand-milled and spray-dried to obtain the composite sodium supplement material.
2. The preparation method according to claim 1, characterized in that: The mass of the nano metal oxide is 1-10% of the mass of the sodium squarate; And / or, based on the total mass of the conductive carbon material and sodium squarate being 100%, the content of the sodium squarate is 50-90%.
3. The preparation method according to claim 1 or 2, characterized in that: The conductive carbon material comprises any one of porous carbon nanotubes, Ketjen black, porous carbon aerogel or graphene, or a combination of at least two thereof; And / or, the nano metal oxide includes any one of MnO2, TiO2, SnO, Al2O3, CuO, ZnO, MoO2, NiO or CoO or a combination of at least two, preferably includes any one of SnO, Al2O3, CuO, ZnO, NiO or CoO or a combination of at least two.
4. The preparation method according to any one of claims 1 to 3, characterized in that The sanding time is 60-240min; and / or, after the sand milling, the D50 of the slurry is 100-500 nm; And / or, the spray drying temperature is 120-200°C.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The slurry also includes a dispersant; Preferably, the added amount of the dispersant is 0.5-2% of the mass of the conductive carbon material; Preferably, the dispersant comprises polyvinyl pyrrolidone and / or polyethylene glycol.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The solvent used in the slurry is water.
7. The preparation method according to any one of claims 1 to 6, characterized in that The preparation method comprises: (1) mixing sodium squarate and a dispersant in water to obtain a saturated aqueous solution; (2) dispersing the conductive carbon material and the nano-metal oxide in the saturated aqueous solution to obtain a mixed slurry; (3) The mixed slurry is sand-milled and spray-dried to obtain the composite sodium supplement material.
8. A composite sodium supplement material obtained by the preparation method according to any one of claims 1 to 7.
9. Use of the composite sodium supplement material according to claim 8 in a sodium ion battery, preferably in a positive electrode sheet of a sodium ion battery.
10. A positive electrode sheet, characterized in that: Comprising a positive electrode active material and the composite sodium supplement material according to claim 8; Preferably, the added amount of the composite sodium supplement material is 0.5-5% of the positive electrode active material.
Citation Information
Patent Citations
Composite sodium supplement additive and application thereof in sodium ion battery
CN113113681A
Alkali metal squarate composite material and preparation method thereof
CN115911387A
Additive for supplementing lithium or sodium as well as preparation method and application of additive
CN116454281A
Sodium supplement slurry and preparation method thereof, positive plate and sodium ion battery
CN117936788A